Quantification of Carbonates, Oxychlorines, and Chlorine Generated by Heterogeneous Electrochemistry Induced by Martian Dust Activity. Issue 4 (16th February 2023) - Wang, Alian; Jackson, Andrew W.; Sturchio, Neil C.; Houghton, Jen; Yan, Chuck Y. C.; Olsen, Kevin S.; Qu, Quincy H. K.
Abstract: Heterogeneous electrochemistry induced by Martian dust activity is an important type of atmosphere‐surface interaction that affects geochemical processes at the Martian surface and in the Martian atmosphere. We have experimentally demonstrated that heterogeneous electrochemistry stimulated by mid‐strength dust events can decompose common chloride salts, which is accompanied by the release of chlorine atoms into the atmosphere and the generation of (per)chlorates (chlorates and perchlorates) and carbonates. In this study, we present quantitative analyses on the above products from 26 heterogeneous electrochemical experiments on chloride salts. Based on these quantifications, our calculation indicates that such atmosphere‐surface interaction during a portion of Amazonian period could accumulate the observed abundance of (per)chlorates, carbonates, and HCl by landed and orbital missions, and thus can be considered as a major driving force of the global chlorine‐cycle on Mars. This study emphasizes the importance of measuring the electrical properties of dust activity on Mars. Plain Language Summary: Frictional electrification is a common process in our solar system, with Martian dust activities known to be a powerful source of electrical charge buildup. Furthermore, the thin atmosphere on Mars makes the breakdown of accumulated electrical fields, in form of electrostatic discharge (ESD), much easier to occur (a hundred times easier than on Earth). ESD generates a huge amount of energetic electrons that collide with Martian atmospheric molecules and generate free radicals. These free radicals react with the Martian chlorides to generate new species. This study found the yields of (per)chlorates, carbonates, and chlorine from the ESD process, with the strength matching mid‐strength Martian dust activity, are at per thousand or percent levels (normalized to the starting chlorides). Based on these results, it is possible to calculate the total yields of those species produced from known chloride sources on Mars by global dust storms during defined durations in the Amazonian period. It was found that the contributions of Mars dust activity can account for the abundances of (per)chlorates, carbonates, and chlorine observed by past and current Mars missions. This study supports that Martian atmosphere‐surface interaction in dust events is a major driving force for the global chlorine‐cycle on Mars. Key Points: Heterogeneous electrochemistry induced by Mars dust activity can decompose chloride, form (per)chlorate, carbonate, and release chlorine This experimental study simulated mid‐strength Mars dust events and revealed the high yields of (per)chlorates, carbonates, and chlorine A calculation based on the results supports Martian dust activity as the major driving force for the global Cl‐cycle in Amazonian period